2004
DOI: 10.1093/ps/83.4.526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age of feed restriction and microelement supplementation to control ascites on production and carcass characteristics of broilers

Abstract: Three experiments were conducted, from January until September 2001, to estimate the optimized age to apply feed restriction to control mortality from ascites, with no negative effects on production and carcass characteristics of broilers. For each experiment, 1,200 1-d-old mixed Ross x Peterson chicks were reared in floor pens (50 chicks in each) and fed commercial feed. Feed restriction was applied for 8 h/d for 14 d at 21 or 28 d of age in experiment 1, 14 or 21 d in experiment 2, and 7 or 14 d in experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 21 publications
7
29
1
2
Order By: Relevance
“…Short-time feed restriction in the early growth stage of broilers has been adopted in commercial broiler production to reduce the mortality rate, the incidence of metabolic disorders such as ascites, lameness, sudden death syndrome and fat deposition (Lippens et al, 2000;Camacho et al, 2004;Pan et al, 2005). Such system results in temporary reduce of growth rate, while the normal weight of broilers can be attained on removal of feed restriction, thus improving the feed efficiency and decreasing the feeding cost (Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Short-time feed restriction in the early growth stage of broilers has been adopted in commercial broiler production to reduce the mortality rate, the incidence of metabolic disorders such as ascites, lameness, sudden death syndrome and fat deposition (Lippens et al, 2000;Camacho et al, 2004;Pan et al, 2005). Such system results in temporary reduce of growth rate, while the normal weight of broilers can be attained on removal of feed restriction, thus improving the feed efficiency and decreasing the feeding cost (Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This result in feed conversion ratio due to feed restriction does not agree with the findings of Lee and Leeson (2001), Dozier et al (2003), Navidshad et al (2006), and Mahmood et al (2007). They observed better conversion values in birds kept under restricted feeding compared to ad libitum fed birds and do not follow the findings of Balog et al (2000), Camacho et al (2004) and Boostani et al (2010) who reported reduced body weight and feed intake of 8 h/ day restricted birds. Aziz (2012) also found that weight gain, feed intake and feed conversion ration of restricted birds were lower than those of control ones.…”
Section: Performance At 21 To 37 Days Oldmentioning
confidence: 55%
“…More studies should be conducted to affirm this suggestion. The insignificant differences in whole carcass and carcass cuts weights between the control and fasted birds follow the findings of Camacho et al (2004), and Mohebodini et al (2009) who found no significant differences in carcass weight and thigh weight between restricted and control birds and do not follow the findings of Mohebodini et al (2009) who found significantly lower carcass weight breast weight compared to that of control birds. The results also do not follow the findings of Boostani et al (2010) who found significantly lower carcass weight and breast weight as compared to those of control birds.…”
Section: Carcass Weightmentioning
confidence: 56%
“…It is known that feed restriction affects chicken performance, leading to a decrease in the weight of the body and some organs, such as the pancreas and those of the digestive tract (Camacho et al, 2004;Wijtten et al, 2010). It can be expected that a decrease in digestive organ mass leads to similar alterations in digestive activity.…”
Section: Introductionmentioning
confidence: 99%